Benzylidene Barbituric Acid Derivatives Shown Anticonvulsant Activity on Pentylenetetrazole-Induced Seizures in Mice: Involvement of Nitric Oxide Pathway - Shabnam Mahernia; Niusha Sharifi; Malihe Hassanzadeh; Nastaran Rahimi; Nastaran Pourshadi; Arash Amanlou; Ahmad Reza Dehpour; Massoud Amanlou (Tabriz University of Medical Sciences, 2018)
ABSTRACT Background: Barbituric acid derivatives have long been used as central nervous system (CNS) suppressants, such as sedatives, hypnotics and anticonvulsants. In addition, previous studies have implicated the involvement of nitric oxide (NO) in the anticonvulsive effects of barbiturates in CNS. Therefore, the purpose of this study was to figure out the effects of a novel class of barbituric acid derivatives on pentylenetetrazole (PTZ)-induced seizures in male mice. Methods: Thirteen synthesized barbituric acid derivatives (a-m) and phenobarbital were administered intraperitoneally (i.p.) 30 min before induction of seizures by PTZ administration. The mechanisms of PTZ-induced seizures in the mice was evaluated using a non-selective nitric oxide synthase (NOS) inhibitor, selective inducible NOS (iNOS) inhibitor, a selective neuronal NOS (nNOS) inhibitor, and NO substrate. Results: Administration of most of the above mentioned derivatives significantly increased the seizures threshold (P<0.001). The most potent derivative (compound a), was chosen in order to investigate the mechanism of action involving in anticonvulsant activity. Administration of a non-selective NOS inhibitor, NG-nitro-L-arginine methyl ester (L-NAME) and a selective nNOS inhibitor, 7-nitroindazole (7-NI) reversed anticonvulsant activity of compound a. However, injection of the nitric oxide precursor, L-arginine (L-Arg) and a selective iNOS inhibitor, aminoguanidine (AG), did not change anticonvulsant activity of the mentioned compound. Conclusion: These results indicated that the NO system, specifically nNOS may contribute to the anticonvulsant activity of benzylidene barbituric acid derivative a. Therefore, this compound is a good candidate in order to designing new anticonvulsant medications